The lost manuscript - Bonidan, Cathy (St. Martin's Press, 2021)
"Cathy Bonidan's The Lost Manuscript is a charming epistolary novel about the love of books and magical ability they have to bring people together. Sometimes a book has the power to change your life... When Anne-Lise Briard books a room at the Beau Rivage Hotel for her vacation on the Brittany coast, she has no idea this trip will start her on the path to unearthing a mystery. In search of something to read, she opens up her bedside table drawer in her hotel room, and inside she finds an abandoned manuscript. Halfway through the pages, an address is written. She sends pages to the address, in hopes of potentially hearing a response from the unknown author. But not before she reads the story and falls in love with it. The response, which she receives a few days later, astonishes her... Not only does the author write back, but he confesses that he lost the manuscript 30 years prior on a flight to Montreal. And then he reveals something even more shocking--that he was not the author of the second half of the book. Anne-Lise can't rest until she discovers who this second mystery author is, and in doing so tracks down every person who has held this manuscript in their hands. Through the letters exchanged by the people whose lives the manuscript has touched, she discovers long-lost love stories and intimate secrets. Romances blossom and new friends are made. Everyone's lives are made better by this book--and isn't that the point of reading? And finally, with a plot twist you don't see coming, she uncovers the astonishing identity of the author who finished the story"--